NOVEL OPTIMAL COORDINATED VOLTAGE CONTROL FOR DISTRIBUTION NETWORKS USING DIFFERENTIAL EVOLUTION TECHNIQUE - Anh, Ho Pham Huy; Kien, Cao Van (Journal of Computer Science and Cybernetics, 2018)
This paper investigates a Distributed Generators (DG) connected to distribution networks offer multiple benefits for power networks and environments in the case of renewable sources. Nevertheless, if there is not an appropriate planning and control strategy, several issues, such as voltage rise problems and increased power losses, may happen. In order to overcome such disadvantages, in this paper, a coordinated voltage control method for distribution networks with multiple distributed generators is proposed. This method is based on a differential evolution DE approach to obtain the optimal setting points for each control component. Furthermore this proposed method considers both of time-varying load demand and production, leading to not only an improvement in the voltage profile but also to optimally minimize the active power loss.